Identifying Risk Profiles for Antisocial Behavior in a Spanish Sample of Young Offenders - López-Romero, Laura (International journal of offender therapy and comparative criminology, 2019)
One of the main purposes of juvenile risk assessment is to distinguish different risk profiles, which may lead to referring youths into specific intervention programs tailored to their specific needs. This study is devoted to identifying main typologies of risk in a sample of 286 Spanish young offenders aged 14 to 22 (M = 17.36; SD = 1.61) years. Participants were classified into different profiles, representing different levels of risk in terms of individual and psychosocial dynamic variables. A three-class (low-, middle-, and high-risk profiles) and a four-class (low-, middle-, high-risk family problems/callous-unemotional (CU) traits, and high-risk impulsive/undercontrolled) solutions were identified. These profiles showed their distinctiveness and meaningfulness in a set of comparisons on antisocial behavior and prior offenses measures. These findings highlight the presence of diverse patterns of risk and suggest that a limited number of specialized interventions may respond to the main needs of most institutionalized youths.